2012
DOI: 10.7200/esicm.142.0432.4i
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of International Competitiveness in the Pharmaceutical Industry

Abstract: Nowadays, the competitiveness of the pharmaceutical industry has been determined by a system or networks involving a variety of factors, therefore is essential to identify them. This study identified and analyzed the variables that impact the competitiveness of the pharmaceutical industry worldwide. We used the Model of Michael Porter for the Competitiveness operationalized with the Global Competitiveness Index of the World Economic Forum and determined which factors affect the international competitiveness in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…The core question of this study is: what are the success surroundings that have led to become internationally competitive in virgin coconut oil industry in Sri Lanka. The previous studies of export competitiveness (Olmeda and Varela (2012) [23] and Daniel (2000)) were based on qualitative approach to collect data. Those studies adopted in-depth, semi-structured interviews with key resource persons to collect primary data.…”
Section: Methodsmentioning
confidence: 99%
“…The core question of this study is: what are the success surroundings that have led to become internationally competitive in virgin coconut oil industry in Sri Lanka. The previous studies of export competitiveness (Olmeda and Varela (2012) [23] and Daniel (2000)) were based on qualitative approach to collect data. Those studies adopted in-depth, semi-structured interviews with key resource persons to collect primary data.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, to take this into consideration, the average total wage in US dollars was utilized from the OECD. As outlined by Cho and Moon (2010), and Olmeda and Sosa Varela (2012) it is important to consider the productivity of workers and therefore the Annual growth rate of output per worker expressed as a percentage was selected. When looking at basic international factors, it was important to look at the Outbound rate of FDI.…”
Section: Factor Conditionsmentioning
confidence: 99%
“…To maximize the effectiveness of R&D programs, shorten drug development and commercialization timelines, pharmaceutical companies are seeking to sophisticate their manufacturing and distribution processes. Therefore, this study implements sophisticated production processes as suggested by Olmeda and Sosa Varela (2012).…”
Section: Firm Strategy Structure and Rivalrymentioning
confidence: 99%
“…The determinants obtained in accordance with the existing literature [Sun et al (2010) and Bakan and Dogan (2012), Watchravesringkan (2012), Olmeda and Varela (2012), Srivastava, Shah and Talha (2006) and Daniel (2000), Oral andMistikoglu (2007), Sun et al, (2010), Shafaei's (2009)] hypotheses have been developed for analysis of this study. In statistical theory, a hypothesis is an unproven proposition or supposition that tentatively explains certain facts or phenomena (Zikmund, 2010, p.499)…”
Section: Hypotheses Developmentmentioning
confidence: 82%
“…The main question of this study is: what are the success conditions that have led to become internationally competitive in tea industry in Sri Lanka. The previous studies of export competitiveness {Watchravesringkan (2012),Olmeda and Varela (2012),Srivastava, Shah and Talha (2006) and Daniel (2000)J were based on qualitative approach to collect data. Those studies adopted in-depth, semi -structured interviews with key resource persons to collect primary data.…”
mentioning
confidence: 99%